DEVELOPMENT OF SOCIAL EDUCATION LEARNING MATERIALS BASED ON LOCAL WISDOM - Aris Suherman (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2021)
ABSTRACT Learning is always interesting to be researched. Learning is a process of active behavior, interactive and constructive when the learning process is used as a social context that needs attention. Social studies learning must be able to become and strengthen the values of local wisdom as a symbol of the students’ character identities. Then there needs to be analyzed the pattern of the development of social science learning materials based on the local wisdom in an effort to shape students’ characters.The purpose of this study is to describe the pattern of the development of social science teaching materials based on the local wisdom. This research was conducted in two approaches, qualitative and quantitative, using two patterns, namely: The Dominant-Lessdominant-Design and the development research design,by carrying out four stages, namely: 1) Initial studies, 2) Preparation of teaching materials, 3) Development of teaching materials and 4) Implementation. The techniques of collectingdata of this research were interviews, questionnaires, observations, tests and documentation. The results of this study can be concluded: 1) The development of social science learning materials based on local wisdom can help teachers to understand students and connect learning materials with the region potentials, 2) The development of social studies learning materials based on local wisdom can help students to understand the potential of their area. This can be seen in the acquisition of research results, the average of pre-test score is 33.70, the average of post-test score is 55.80, there was an increase average about0.35. It is in the sufficient categorized. Keywords : Local wisdom, social studies, learning materials. ABSTRAKPembelajaran merupakan persoalan yang senantiasa menarik untuk dilakukan penelitian. Pembelajaran adalah sebagai proses prilaku aktif, interaktif dan konstruktif manakala proses pembelajaran ini dijadikan sebagai kontekssosial yang perlu mendapat perhatian. Pembelajaran IPS harus mampu menjadi dan menguatkan nilai-nilai kearifan local sebagai symbol identitas karakter anak didik. Maka perlu adanya analisa pola pengembangan materibahan ajar pembelajaran IPS berbasis kearifan local dalam upaya pembentukan karakter siswa. Tujuan dari penelitian ini adalah untuk mendiskripsikan pola pengembanagn bahan ajar pendidikan IPS berbasis kearifan lokal. Penelitian ini dilakukan dua pendekatan yaitu kualitatif dan kuantitatif dengan menggunakan dua pola yaitu : The Dominant-Less-Desaign dan Desaign research and development. Dengan melakukan empat tahapan yaitu : 1) Studi awal, 2) Penyusunan bahan ajar, 3) Pengembangan materi bahan ajar dan 4) Implementasi. Teknik pengumpulan data penelitian ini yaitu dengan wawancara, kuesioner, observasi, tes dan dokumentasi. Hasil penelitian ini dapat disimpulkan: 1) Pengembangan materi pembelajaran IPS berbasis kearifan local dapat membantu guru dalam upaya pemahaman siswa dan menghubungkan materi pembelajaran dengan potensi wilayah. 2) Pengembangan materi bahan ajar pembelajaran IPS berbasis kearifan local dapat membantu siswa terhadap peningkatan pemahaman potensi daerahnya. Hal ini dapat dilihat pada perolehan hasil penelitian yaitu: dari rata-rata skor pree test 33.70 menjadi 55.80. Ada peningkatan rata-rata 0.35, walaupun pada kategori cukup atau sedang. Kata Kunci :Kearifan lokal, Ilmu Pengetahuan Sosial, Materi pembelajaran.